Efektivitas Penyuluhan Menggunakan Slide Show dan Video Clip Tentang Narkoba terhadap Pengetahuan dan Sikap Siswa Kelas 9 SMPN 1 Kabupaten Kaur - Elwindra Elwindra; Agustina Agustina; Ahmad Farid Umar (Jurnal Persada Husada Indonesia, 2017)
Patients with narcotics addiction and illegal drugs in general are teenagers aged 15-24years old. Curiosity and the intensity sense of wanting to try in adolescents thus making them vulnerable to narcotics. For that, it is essential to do early prevention to prevent them from using narcotics. This study is a quasi-experiment aimed to determine the effectiveness of counseling on drug using Slide shows and Video clips media to improved the knowledge and attitude of grade 9 students of SMPN 1 Kaur Year 2017. The population in the study were students in grade 9 class of SMPN 1 Kaur, with samples of 36 students. This study began in January 2017 until April 2017. Data obtained through questionnaires given through pre and post tests which was then analyzed by Paired T Test at the level of 95%. From the analysis it was found that there is the influence of education on drug using slide shows and video clips media to increase knowledge (p = 0.001) and attitude (p = 0.003). School authorities were recommended to provide information to students about drugs in the learning process and for parents and the police to cooperate in the prevention and provision of information about students’ involvement in narcotics.